Odpowiedź :
Odpowiedź:
d. 2*x=12-2*x
2x = 12 - 2x
2x + 2x = 12
4x = 12
x = 12/4
x = 3
Sprawdzenie
2*3=12-2 * 3
6 = 12 - 6
6 = 6
L=P
------------------------------------------
b. 7*x-4=9+8*x
7x - 4 = 9 + 8x
7x - 8x = 9 + 4
-x = 13
x = -13
Sprawdzenie
7*x-4=9+8*x
7 * (-13) - 4 = 9 + 8 * (-13)
-91 - 4 = 9 + (-104)
-95 = -95
L=P
--------------------------------
c. -5+7*x=2*x-20
-5 + 7x = 2x - 20
7x - 2x = -20 + 5
5x = -15
x = -15/5
x = -3
Sprawdzenie
-5+7* (-3) =2* (-3) -20
-5 - 21 = -6 - 20
-26 = -26
L=P
--------------------------
a. 5*x-3+2*x=4*x+9
5x - 3 + 2x = 4x + 9
7x - 3 = 4x + 9
7x - 4x = 9 + 3
3x = 12
x = 12/3
x = 4
Sprawdzenie
5*x-3+2*x=4*x+9
5 * 4 - 3 + 2 * 4 = 4 * 4 + 9
20 - 3 + 8 = 16 + 9
25 = 25
L=P
Szczegółowe wyjaśnienie:
ODPOWEIDŹ
Mam nadzieję że pomogłam
![Zobacz obrazek Zuziabalinska2007](https://pl-static.z-dn.net/files/d35/f05381f4322eb5507324b3e4eda2f3dd.jpg)